Sociomathematical Norm, Mathematical Resilience and Mathematical Representation Ability in Mathematics Learning - Samsul Maarif; Harita Audhea Akbari (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
The abstract nature of mathematics needs to be represented in various comprehensive representations of mathematics itself. One of the soft skills that can support mathematical representation ability is sociomathematical norm and mathematical resilience. This study aims to analyze the effect of sociomathematical norms and resilience on mathematical representation ability in learning. The method used in this study is quantitative with a correlational design using survey techniques and question model structures. The sample used was 100 junior high school students using proportional random sampling techniques. The mathematical representation ability test instrument consists of 5 test items. Meanwhile, the sociomathematical norm instrument is in the form of a questionnaire with a Likert scale. Data analysis was carried out using structural equation modelling (SEM) with n student t-tests to determine the influence between variables using SmartPLS software. The results of testing the mathematical representation ability instrument, sociomathematical norm and mathematical resilience showed that the indicators on each instrument were said to be valid. The reliability test results showed that all instruments met the reliability requirements. The results of the hypothesis testing show that there is a significant favourable influence of sociomathematical norms on mathematical representation ability, there is a significant favourable influence of mathematical resilience on mathematical representation ability, and there is a significant favourable influence of sociomathematical norms on mathematical representation with mathematical resilience mediation.